Distinct p53 phosphorylation patterns in chronic lymphocytic leukemia patients are reflected in the activation of circumjacent pathways upon DNA damage - Mancikova, Veronika; Pesova, Michaela; Pavlova, Sarka; Helma, Robert; Zavacka, Kristyna; Hejret, Vaclav; Taus, Petr; Hynst, Jakub; Plevova, Karla; Malcikova, Jitka; Pospisilova, Sarka (Molecular oncology, 2023)
TP53 gene abnormalities represent the most important biomarker in chronic lymphocytic leukemia (CLL). Altered protein modifications could also influence p53 function, even in the wild-type protein. We assessed the impact of p53 protein phosphorylations on p53 functions as an alternative inactivation mechanism. We studied p53 phospho-profiles induced by DNA-damaging agents (fludarabine, doxorubicin) in 71 TP53-intact primary CLL samples. Doxorubicin induced two distinct phospho-profiles: profile I (heavily phosphorylated) and profile II (hypophosphorylated). Profile II samples were less capable of activating p53 target genes upon doxorubicin exposure, resembling TP53-mutant samples at the transcriptomic level, whereas standard p53 signaling was triggered in profile I. ATM locus defects were more common in profile II. The samples also differed in the basal activity of the hypoxia pathway: the highest level was detected in TP53-mutant samples, followed by profile II and profile I. Our study suggests that wild-type TP53 CLL cells with less phosphorylated p53 show TP53-mutant-like behavior after DNA damage. p53 hypophosphorylation and the related lower ability to respond to DNA damage are linked to ATM locus defects and the higher basal activity of the hypoxia pathway.
Keywords: nádorový supresorový protein p53; poškození DNA; Phosphorylation; ATM protein; Ataxia Telangiectasia Mutated Proteins; chronická lymfatická leukemie; DNA Damage; hypoxie; fosforylace; doxorubicin; Doxorubicin; Hypoxia; Humans; Tumor Suppressor Protein p53; Leukemia, Lymphocytic, Chronic, B-Cell; geny p53; lidé; Genes, p53